Different effect of smoking on genders in Crohn’s disease - Karczewski, Jacek; Poniedzialek, Barbara; Piotr, Rzymski; Malgorzata, Mazur (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Smoking is a well-established environmental risk factor in Crohn’s disease (CD). The study was aimed to investigate possible gender differences in the effect of smoking on the course of CD, with a special focus on selected immune parameters such as Th1/Th2/Th17 cytokines and regulatory T cells (Tregs). Materials and Methods: A group of 55 adults with CD was enrolled to the study. The analysis of clinical, demographic and immunological characteristics of patients was performed according to their smoking status and gender. Values were considered significant when p≤0.05. Results: Patients who smoked, particularly females, more frequently suffered from a moderate-to-severe form of the disease, requiring glucocorticoid and immunosuppressive therapies. Smokers, particularly females, were also hospitalized and underwent surgeries more frequently than non-smokers. Cytometric analysis showed higher levels of serum proinflammatory cytokines and lower levels of peripheral Tregs in female smokers and former smokers, comparing to males from these subgroups. Conclusion: Presented results demonstrate that in all investigated subgroups, particularly however among current smokers and former smokers, female patients seemed to be more affected by CD. Females developed more severe form of the disease and experienced the onset earlier than men. The imbalance between pro- and anti-inflammatory factors observed in CD patients was also more distinct in female smokers and former smokers, comparing to males, and could substantially contribute to the severity of the disease. Exposure to smoking seems to be one of the environmental factors contributing to the gender differences in CD.